Enseignement bi-plurilingue au Mali : former et sensibiliser les enseignants de classes bilingues - Laurent Coulibaly (Recherches en didactique des langues et des cultures)
Faced with the low yield of the monolingual classical school inherited from the colonial era with French as the only medium and object of teaching and learning, Mali has embarked since the early 1980s on a policy of bi-plurilingual education combining local languages and French. Many studies (Dabène, 1994; Cummins, 2001; Vilpoux and Blanchet, 2015; Maurer, 2007, 2011a, 2013b, 2016, 2018) agree on the pedagogical advantages of a bilingual education system taking into account the learner’s first language, or at least one of their first languages. The aim of this bi-plurilingual education policy is to get learners to carry out their first learning in a language of their social and/or family environment (language 1) so that subsequent learning in French (language 2) is facilitated. However, despite the encouraging results of different phases of experimentation that have shown a clear advantage of bilingual schools over monolingual traditional one (Nounta, 2015; ELAN-Afrique, 2016), bilingual education in Mali faces obstacles that hinder its development. The issue of teacher training and their low adherence to bi-plurilingualism in schools are major obstacles in this respect. This contribution is based on a field survey as part of a doctoral research project conducted from January to August 2020 in four bilingual elementary schools in the city of Bamako. The field survey, which focused on the issue of teacher training in bi-plurilingual teaching and their sociolinguistic representations, confirms teachers’ attitudes of resistance to the teaching of local languages in a sociolinguistic situation where linguistic imaginations are influenced by the language market (Calvet, 2002; 2017). Moreover, as training in bi-plurilingual teaching is absent from their initial training, teachers feel a lack of training and report difficulties in their classroom practices. Based on data obtained from semi-structured interviews (Blanchet, 2012) with teachers and educational authorities, we conduct a content analysis (Blanchet and Gotman, 2015), reporting on the state of training and adherence of teachers, and then make proposals for improvement.